Analysis of Growth and Poverty In India: Analyzing the Relationship Between Growth, Poverty, and Development in Indian States (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The main objective ofthis paper is to analysis differences in poverty levels across states in India during the period1991 -2001. In doing so, it seeks to focus on inter-state differences in economic growth as an explanation. The important objective of the study is to find out the relationship and significanceof physical infrastructure and human resource development in reducingpoverty.       The results  of  the  study  prove  that relationship between  poverty and Infrastructure  Development Index (IDI ) as weekendover time, whereas           the relationship of poverty with Human Resource Development Index  (HDI) has  got stronger overtime. Thus, human development has become more relevant for poverty alleviation than infrastructure development between states. This paper attempt to usingdata from Economic survey of India(2003-04), CMIE Basic Statistics,Sept. 1994. Lastly the reachedconclusion and suggestion.